Analisis kelembaban udara dan tingkat kenyamanan lingkungan kos-kosan di area sekitar kampus UIN Jakarta - Suwarna , Iwan Permana; Pramudita, Finna; Yulianto, Riski; Tamala, Lastri Dewi; Syamila, Hilwa; Nurfadillah, Syahriani; Ramadhan, Purwo Harris (Universitas Ahmad Dahlan, 2025)
This study aims to analyze the humidity levels and their impact on the comfort ofboarding house residents around UIN Syarif Hidayatullah Jakarta campus. Boardinghouses, as temporary residences for students, play a vital role in supportingacademic success, where environmental quality, especially thermal comfort, iscrucial. This research employs a quantitative approach with descriptive andcorrelational methods. Data collection was conducted by measuring humidity levelsusing a digital psychrometer in several boarding houses around Campus 1, Campus2, and Campus 3 of UIN Jakarta. The variables examined include humidity (%RH) asthe independent variable, and the comfort level of residents as the dependentvariable. Data were analyzed using descriptive statistics to describe the humiditylevels and compare them with Indonesia's thermal comfort standards, whichcategorize comfort based on temperature and humidity. The results showed that thehumidity levels in most boarding houses fell into the